Global Distribution and Evolution of Mycobacterium bovis Lineages - Zimpel, Cristina Kraemer; Patané, José Salvatore L.; Guedes, Aureliano Coelho Proença; de Souza, Robson F.; Silva-Pereira, Taiana T.; Camargo, Naila C. Soler; de Souza Filho, Antônio F.; Ikuta, Cássia Y.; Neto, José Soares Ferreira; Setubal, João Carlos; Heinemann, Marcos Bryan; Guimaraes, Ana Marcia Sa (Frontiers in Microbiology, 2020)
Mycobacterium bovis is the main causative agent of zoonotic tuberculosis in humans and frequently devastates livestock and wildlife worldwide. Previous studies suggested the existence of genetic groups of M. bovis strains based on limited DNA markers (a.k.a. clonal complexes), and the evolution and ecology of this pathogen has been only marginally explored at the global level. We have screened over 2,600 publicly available M. bovis genomes and newly sequenced four wildlife M. bovis strains, gathering 1,969 genomes from 23 countries and at least 24 host species, including humans, to complete a phylogenomic analyses. We propose the existence of four distinct global lineages of M. bovis (Lb1, Lb2, Lb3 and Lb4) underlying the current disease distribution. These lineages are not fully represented by clonal complexes and are dispersed based on geographic location rather than host species. Our data divergence analysis agreed with previous studies reporting independent archeological data of ancient M. bovis (South Siberian infected skeletons at ~2,000 years before present) and indicates that extant M. bovis originated between 715 and 3,556 years BP, with later emergence in the New World and Oceania, likely influenced by trades among countries.